2019
DOI: 10.29173/cjs29599
|View full text |Cite
|
Sign up to set email alerts
|

Re-Inscribing Gender Relations through Employment-Related Geographical Mobility: The Case of Newfoundland Youth in Resource Extraction

Abstract: Despite the popular representation of the masculine hero migrant (Ni Laoire, 2001), rural youth scholars have found that young men are more likely to stay on in their communities, while young women tend to be more mobile, leaving for education and better employment opportunities elsewhere (Corbett, 2007b;Lowe, 2015). Taking a spatialized approach (Farrugia, Smyth & Harrison, 2014), we contribute to and extend the rural youth studies scholarship on gender, mobilities and place by considering the case of young N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In fact, the movement of youth away from rural places has been called a migration or mobility "imperative" (Corbett, 2005;Farrugia, 2016). This body of work has also found that rural to urban moves are gendered and classed (Bjarnason & Thorlindsson, 2006;Power & Norman, 2019). For example, employment in rural areas tends to be concentrated in male-dominated sectors, including resource extraction and agriculture, which favour young men and enable pathways for mobilities to other places with similar industries.…”
Section: Transitions Mobilities and Precaritymentioning
confidence: 99%
“…In fact, the movement of youth away from rural places has been called a migration or mobility "imperative" (Corbett, 2005;Farrugia, 2016). This body of work has also found that rural to urban moves are gendered and classed (Bjarnason & Thorlindsson, 2006;Power & Norman, 2019). For example, employment in rural areas tends to be concentrated in male-dominated sectors, including resource extraction and agriculture, which favour young men and enable pathways for mobilities to other places with similar industries.…”
Section: Transitions Mobilities and Precaritymentioning
confidence: 99%
“…Both Corbett (2007a) and Norman and Power (2015) found that for young women living in Atlantic Canada, upward mobility was associated with outward mobility, especially in terms of formal education. In a more recent study, Power and Norman (2019) examine how gender relations in rural areas inform possible mobilities, particularly in the context of resource extraction industries. Embedded practices over the life course result in conventions of men working outdoors with their hands, and in contrast, women working indoors, often in positions where they provide care and services to others.…”
Section: Youth Outmigration From Shrinking Placesmentioning
confidence: 99%